2022
DOI: 10.3390/agriculture12111775
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals the Key Genes Involved in Lipid Deposition in Pekin Ducks (Anas platyrhynchos domesticus)

Abstract: There are differences in lipid deposition in fatty-type (FT) and lean-type (LT) ducks. Fatty ducks have a higher rate of sebum and abdominal fat, lower meat yield and hepatic lipid contents than LT ducks. However, the underlying changes in gene expression profiles regarding the lipid deposition between FT and LT ducks have not yet been clarified. To identify the differentially expressed genes in the liver, sebum, and abdominal fat between both ducks, we identified the gene expression profiles in the liver, seb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Of the 19 trait-associated genes identified, 13 genes are expressed in feather bulb tissues (Jiang et al, 2020). They included STARD9, ZNF106, BANP, ZNF827, SCGN, TTBK2, TRIM66, ZCCHC14, PHLPP1, KLHDC4, IPMK, PLXNA2, and CAMK1G.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 trait-associated genes identified, 13 genes are expressed in feather bulb tissues (Jiang et al, 2020). They included STARD9, ZNF106, BANP, ZNF827, SCGN, TTBK2, TRIM66, ZCCHC14, PHLPP1, KLHDC4, IPMK, PLXNA2, and CAMK1G.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that chicken chocolate feather color is a sex-linked recessive phenotype associated with missense mutations in TYRP1 [29,62]. Jiang et al showed that the downregulation of genes such as TYRP1 in a duck's feather follicles probably contributes to a duck's white feathers [63]. Xu et al found that the mRNA expression levels of TYRP1 genes correlated with the color of the black feathers of the Holdobaggy goslings, and the initial feather color can be used to identify the sex [31].…”
Section: Feather Color Traitmentioning
confidence: 99%